Development of i-spring learning media about animal life cycle for primary schools students - Amelia, Rizki; Aini, Aniswatul Lathifah; Irambona, Alfred (Journal of Environment and Sustainability Education, 2024)
The science learning process will be more meaningful if it includes facts, concepts, scientific ways of thinking, and solving problems. Meaningful learning will make it easier for students to understand science concepts. Material on animal life cycle and environmental conservation is one of the materials studied at the elementary school level. In general, students find it difficult to learn the material because the material is abstract. I-Spring learning media can help contextualize abstract material and increase learning effectiveness. This research aims to develop I-Spring-based learning media products on animal life cycle materials and environmental preservation for elementary school students. This research is a developmental research using the ADDIE development model. The research procedure consists of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 20 grade 4 students of SDN Tanjungrejo Malang City. The results of media validation showed a score of 91.74%, material validation was 96.18%, and learning validation was 94.04% while the attractiveness of I-Spring learning media products obtained a score of 90.55%. Thus, learning media is very feasible to use to support the effectiveness of the science learning process.